Respuesta :
Answer:
(4xc)-6=2 then c=2
Step-by-step explanation:
because we knew that we had to do 6+2=8 so then 8 divided by 4 = 2 so the answer would be 2!
Answer:
(4c) - 6 = 2
4c - 6 = 2
c = 2
Both equations will work.
Step-by-step explanation:
"The product of 4 and a number" is the same as 4 times that number.
Since the missing number is to be said as c, the correct term for this is 4c
6 less than (4c) is the same as (4c) - 6
We have the left-hand-side of the equation as (4c) - 6
The right-hand side is 2
- (4c) - 6 = 2
- or
- 4c - 6 = 2
Now, we have to solve for c.
-Chetan K